1999
DOI: 10.1002/tl.8006
|View full text |Cite
|
Sign up to set email alerts
|

Development and Adaptations of the Seven Principles for Good Practice in Undergraduate Education

Abstract: These principles have been among the most influential ideas of the past twenty years. They have been disseminated and applied in many different ways, as this chapter illustrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
146
1
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(165 citation statements)
references
References 6 publications
8
146
1
10
Order By: Relevance
“…It was also found that for students in need of intensive feedback, differential feedback is likely to lead to the development of individual abilities of students to assess their achievements and to reinforce their academic confidence. This finding emerged also from previous studies Birch, 2013;Bransford et al, 2000;Bruff et al, 2013;Chickering & Gamson, 2000;Francis & Shannon, 2016;Garrison et al, 2001;Olivier, 2016;Poon, 2013;Tan, 2016;Tempelaar et al, 2015;Zilka & Zeichner, 2017).…”
Section: Teacher Presencesupporting
confidence: 85%
See 1 more Smart Citation
“…It was also found that for students in need of intensive feedback, differential feedback is likely to lead to the development of individual abilities of students to assess their achievements and to reinforce their academic confidence. This finding emerged also from previous studies Birch, 2013;Bransford et al, 2000;Bruff et al, 2013;Chickering & Gamson, 2000;Francis & Shannon, 2016;Garrison et al, 2001;Olivier, 2016;Poon, 2013;Tan, 2016;Tempelaar et al, 2015;Zilka & Zeichner, 2017).…”
Section: Teacher Presencesupporting
confidence: 85%
“…They have found that the creation of a learning environment that supports the students and is attentive to their needs, and the creation of a "learning community" greatly influence the delivery of the course and the quality of both the learning and the teaching processes. Numerous studies Bransford, Brown, & Cocking, 2000;Chickering & Gamson, 2000;Garrison, 2007;Garrison et al, 2001) have shown that one of the most important factors in the success of teaching and learning processes is "teacher presence" in both VCs and BCs. Teacher presence is defined as meaningful communication for shaping, assisting in, and directing cognitive and social processes.…”
Section: Teacher Presencementioning
confidence: 99%
“…To determine practices with positive impacts on students at the postsecondary level, Chickering and Gamson (1987) synthesized decades of research to develop "…seven broad principles for good practice in undergraduate education" (Cruce, Wolniak, Seifert, & Pascarella, 2006, p. 365). Chickering and Gamson (1999) also sought to set forth accessible, synthesized evidence for faculty, administrators, higher education agencies, and policymakers. The principles were developed with practicality and understandability in mind.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Additional studies might be undertaken to solicit rubrics from institutions and organizations. Chickering and Gamson (1999) worked to produce a framework that was "accessible, understandable, practical, and widely applicable" (p. 76). Future studies could also investigate the use of a rubric that assesses for the Seven Principles and its impact on student satisfaction and learning.…”
Section: Discussionmentioning
confidence: 99%